Comparison of clinical outcomes in anterior cervical discectomy versus foraminotomy for brachialgia. (2nd January 2019) - Foster, Mitchell T.; Carleton-Bland, Nicholas P.; Lee, Maggie K.; Jackson, Richard; Clark, Simon R.; Wilby, Martin J.
Abstract: Aim: The choice between anterior cervical discectomy & fusion (ACD) or posterior cervical foraminotomy (PCF) for the treatment of cervical brachialgia is controversial. This study aimes to compare clinical outcomes between these two operative inteventions for brachialgia. Methods:Retrospective review of prospectively collected data was performed. Patients receiving a primary ACD or PCF to treat brachialgia, in a single tertiary neurosurgical unit were included. Surgical details, and patient reported outcomes (COMI-Neck questionnaire) were extracted from a prospectively maintained spinal procedure database. Minimum clinically important difference (MCID) was defined as a change in COMI score of –2 at 12 months. The student t-test, Chi-square test, and linear regression were used to compare groups.Results: Between June 2011 ad February 2016 there were 634 ACD procedures (Median age 49; 321 Male), and 54 PCF procedures (Median age 50; 37 Male) perfomed for brachialgia. Age, ASA and pre-operative COMI were similar between the groups (p > .05). Complete outcome data was recorded at twelve months in 312 ACD and 36 PCF patients. Both ACD and PCF were associated with an improvement in COMI at 3 and 12 months (all p < .01). Mean change in COMI at 3 months was –2.38 for ACD, versus –2.31 for PCF (p = .88); at twelve months it was –2.94 for ACD, versus –2.67 for PCF (p = .55). MCID was seen in 59% of ACD cases, versus 58% of PCF cases at twelve months (p = .91).Conclusion: There was no significant difference between outcomes in the ACD and PCF groups. This is supportive of published literature. The proposed multicenter RCTs may inform further.